KAJIAN HUKUM TENTANG PENYELESAIAN TINDAK PIDANA ANAK BERDASARKAN DIVERSI POLRESLABUHANBATUSELATAN - Barryansyah Daulay (NERACA KEADILAN, 2025)
The background of this research is to examine the implementation of child diversion at the South Labuhan Batu Police Resort, including the mechanisms, obstacles encountered, and efforts made to overcome these obstacles. Therefore, this study uses normative juridical research using empirical data obtained in the field. The research findings are the stages of diversion implementation at the South Labuhan Batu Police Resort, through the identification and initial investigation stages. After a case involving a child is received, investigators will conduct an investigation considering the child's best interests. Then, there is the diversion deliberation: Investigators facilitate deliberation to reach an agreement between the relevant parties. Once an agreement is reached, the results are submitted to the court. The obstacles faced in implementing diversion as a form of resolving juvenile crimes at the South Labuhan Batu Police Station include legal regulations that do not fully support the Juvenile Criminal Justice System Law which still needs to be refined. Negative perceptions often arise, with the public often holding negative views of the diversion mechanism, thus perceiving it as a form of injustice or impunity. Other factors include limited skilled human resources due to rotation of duties and limited mediation facilities or space, which leads to long queues. To overcome these obstacles, the involvement of Bhabinkamtibmas (Community Police Officers) in the case resolution process is necessary, facilitating a community approach and peaceful resolution at the local level. Furthermore, outreach to internal law enforcement officers and the general public regarding the importance of handling children differently from adults and the benefits of restorative justice to avoid stigmatization of children is also needed. Furthermore, implementation of the Republic of Indonesia National Police Regulation (Perkap) Number 8 of 2021 concerning Handling of Criminal Acts Based on Restorative Justice is crucial. Finally, coordination with stakeholders through mitigation meetings for criminal cases against children and women is crucial for prompt handling and ensuring that the implementation of diversion meets the stipulated requirements.